2002
DOI: 10.1097/00004356-200209000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density in patients with stroke

Abstract: The objectives of this study were to investigate the development and pathogenesis of osteoporosis in stroke in-patients, to compare the bone mineral density (BMD) of the paretic and non-paretic sides, to study longitudinal changes during the period on the rehabilitation ward and to relate BMD to demographic, impairment and disability variables. Participants were 32 first-stroke in-patients (19 men), with an average age of 62.4 +/- 8.1 years. Demographic and clinical characteristics were documented. The BMD of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 17 publications
5
30
0
1
Order By: Relevance
“…Previous studies in stroke patients have reported 1.3-8.8% side-to-side difference in BMD at various sites in the legs [15,16,20,22,23,[50][51][52]. However, comparison with other studies is extremely difficult for several reasons.…”
Section: Side-to-side Differences In Bone Mineral Levels and Soft Tismentioning
confidence: 96%
See 2 more Smart Citations
“…Previous studies in stroke patients have reported 1.3-8.8% side-to-side difference in BMD at various sites in the legs [15,16,20,22,23,[50][51][52]. However, comparison with other studies is extremely difficult for several reasons.…”
Section: Side-to-side Differences In Bone Mineral Levels and Soft Tismentioning
confidence: 96%
“…First, these studies reported data from patients in different stages of stroke recovery such as acute [22], subacute [15,23,50,51], and chronic [15,50]. Second, many studies included subjects who were non-ambulatory [16,20,22,51,52]. Third, BMD was measured at different sites in the lower extremity in different studies such as femoral neck [15,20,51,52], trochanter [20], proximal femur [16], total femur [16], first metatarsus [21] and whole leg [6,50].…”
Section: Side-to-side Differences In Bone Mineral Levels and Soft Tismentioning
confidence: 99%
See 1 more Smart Citation
“…Following a stroke, individuals can have a multitude of impairments that result in compromised functional status, low physical activity, reduced use of the paretic arm and leg, and consequently bone loss overall that is greater on the paretic side. In persons with stroke, BMD on the paretic side has been correlated with muscle strength [38][39], muscle atrophy [38,40], degree of motor recovery [41][42][43][44], cardiovascular fitness [40], ability to perform functional activities [42,[44][45], walking ability [46], weight-bearing ability [47], and amount of skeletal loading [48]. The nonparetic side may also sustain a certain degree of bone loss that is less pronounced when compared with the paretic side [46][47]49].…”
Section: Stroke: a Model Of Disuse Osteoporosismentioning
confidence: 99%
“…Of these fractures, 27-36% occur in the upper extremity [1,3]. Decreased use of the paretic upper extremity due to various impairments such as muscle weakness, spasticity and reduced motor skills may lead to secondary complications, such as bone loss and muscle atrophy [4][5][6][7][8][9]. In addition, individuals with stroke also have a higher risk of falls than the age-matched population [10].…”
Section: Introductionmentioning
confidence: 99%